Otimização da rota de linhas de transmissão utilizando uma metodologia de avaliação multicritério - Nóbrega , Igor Jasmim da (2019)
This work presents a method of multicriteria evaluation of transmission line tracing in order to minimize the project implementation costs. In the work, Geographic Information Systems (GIS) tools are used to obtain the matrices of each evaluated criterion. For the multicriteria analysis, the AHP technique is used to determine the weights of the criteria considered (Alachated Areas, Permanent Preservation Areas, Airports, Structure, Hydrography, Navigable Rivers, Highways, National Interconnected System, Conservation Units and Land Use). After this, the cost surface, or friction surface, of the studied site is obtained. With this surface, a graph algorithm is applied to determine the optimized route of the transmission line, which is the final product of the present work.